La pratique funéraire du dépôt de seaux en bois à la période mérovingienne : un état de la question en Gaule du Nord-Ouest - Amélie Vallée (Archéologie Médiévale)
The presence of wooden buckets with a metal frame in some graves from the end of the Late Antiquity and the Merovingian period in northwestern Gaul has intrigued scientists since the 19th century. This article proposes to present the current state of knowledge based on more than two hundred examples found in an area from the mouth of the Rhine to the north of the Seine. A typochronology was worked out for the vessel dating from the end of the 4th century to the end of the 7th century. The analyses of wood and metallic elements give further information on their production. The typology and the analysis carried on the spatial distribution of these buckets allow to consider the question of production, diffusion and exchanges. The morphological characteristics of some artifacts discovered beyond the Channel perfectly illustrate the contacts between the Anglo-Saxon and Merovingian populations. The study of these funerary contexts shows the richness of grave goods. Finally, a synthesis of all these elements leads to consider the function of this vessel.